Antiangiogenesis: vessel regression, vessel normalization, or both?: Cancer research landmarks - Augustin, Hellmut; Koh, Gou Young (Cancer research, 2022)
The concepts of antiangiogenic tumor therapy were pioneered on the assumption that the inhibition of tumor angiogenesis should lead to the complete regression of the tumor-associated vasculature and thereby hold the tumor in an avascular dormant state. Yet, clinical trials revealed limited efficacy of angiogenesis inhibitors when used as monotherapy. Instead, antiangiogenic drugs proved effective to extend overall survival when used in combination with chemotherapy. This counterintuitive observation—inhibition of tumor vascularization should lead to less and not more delivery of chemotherapy to the tumor—led to the concepts of “vessel normalization.” This refers to the notion that antiangiogenic drugs prune the most immature tumor vessels and spare mature vessels, thereby resulting in a more normal-appearing vasculature that leads to better access of chemotherapy to the tumor. The concepts of vessel normalization were first laid out in a landmark publication in Cancer Research in 2004. More than 600 studies on different aspects of vessel normalization have been published since then. Nevertheless, it is to this day less clear than ever to what extent vessel regression (leading to tumor starvation) and vessel normalization (facilitating chemotherapy) contribute to the clinical efficacy of antiangiogenic tumor therapy. This “Landmark Commentary” puts the concepts of tumor vessel normalization in historical context and develops thereupon some of the most burning questions in the field of translational angiogenesis research that need to be answered to further advance the application of tumor vascular stroma reprogramming therapies.See related article by Tong and colleagues, Cancer Res 2004;64:3731-6.
Gesehen am 31.01.2023